Promoting artificial meat to improve food security and reduce resource-environment pressure: is it practicable in China? - Yang, Minda; Min, Shi; Nguyen, Trung Thanh; Qing, Ping (Frontiers in Sustainable Food Systems, 2024)
This study aims to understand the practicability of promoting artificial meat consumption to achieve the dual goals of improving food security and reducing resource-environment pressure by evaluating Chinese consumers’ willingness to pay (WTP) for artificial meat. A discrete choice experiment was conducted through an online survey with 998 consumers in five representative cities in China to examine their preferences and WTP for artificial meat. A random information intervention was incorporated to assess the effects of providing positive information related to artificial meat on consumers’ choice. The estimation results show significantly lower WTP for both cultured and plant-based meat compared to farm-raised meat, with plant-based meat receiving higher WTP than cultured meat. The information intervention significantly reduces the WTP disparity between artificial and farm-raised meat. The findings reveal that the marketing of artificial meat in China faces significant challenges, and the practicability of promoting its consumption to achieve food security and environmental sustainability goals is currently limited. This study supplements the literature on Chinese consumers’ attitudes toward artificial meat and provides an essential reference for policy design of promoting the consumption of artificial meat.